2006
DOI: 10.1038/sj.bjc.6603231
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of second malignancies after in situ breast carcinoma in a population-based registry

Abstract: Among 1276 primary breast carcinoma in situ (BCIS) patients diagnosed in 1972 -2002 in the Southern Netherlands, 11% developed a second cancer. Breast carcinoma in situ patients exhibited a two-fold increased risk of second cancer (standardised incidence ratios (SIR): 2.1, 95% confidence interval (CI): 1.7 -2.5). The risk was highest for a second breast cancer (SIR: 3.4, 95% CI: 2.6 -4.3; AER: 66 patients per 10 000 per year) followed by skin cancer (SIR: 1.7, 95% CI: 1.1 -2.6; AER: 17 patients per 10 000 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 21 publications
1
22
1
Order By: Relevance
“…Thus, the well-studied effects of radiotherapy appear to hold true in an observational setting. However, our findings are in contrast with those of Soerjomataram et al (2006), who found (also in an observational setting) that both ipsilateral and contralateral invasive breast cancer risks were slightly higher in BCIS patients who received radiotherapy.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Thus, the well-studied effects of radiotherapy appear to hold true in an observational setting. However, our findings are in contrast with those of Soerjomataram et al (2006), who found (also in an observational setting) that both ipsilateral and contralateral invasive breast cancer risks were slightly higher in BCIS patients who received radiotherapy.…”
Section: Discussioncontrasting
confidence: 56%
“…On the other hand, Franceschi et al (1998) found no excess risk at any cancer site other than the breast. Soerjomataram et al (2006) studied subsequent ipsilateral and contralateral breast cancers separately, and found the increased risks to be similar (SIR for ipsilateral 1.9; contralateral 2.0) -although each of these figures was based on a per-person rather than per-breast calculation and should therefore be doubled in order to be directly comparable with our SIR estimates.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Rawal et al (2005) analysed ipsilateral and contralateral breast cancers separately, but it appears that mastectomies were not accounted for. Similarly, Soerjomataram et al (2006) calculated expected numbers and SIRs for breast cancer following breast carcinoma in situ separately for ipsilateral and contralateral tumours, but it is not clear whether they allowed for mastectomies. Moreover, they applied the overall incidence rates from the general population to each group (rather than half-rates), thus leading to expected numbers which were twice, and SIRs which were half, the true values.…”
mentioning
confidence: 99%